Molecular characterization and mRNA expression of grp78 and hsp90A in the estuarine copepod Eurytemora affinis - Xuereb, Benoit (Springer Netherlands, 2012)
The present study aimed to develop a method of quantification of heat shock protein transcript levels in the estuarine copepod Eurytemora affinis. For that, the full-length cDNA of the 78-kDa glucose-regulated protein (Ea-grp78) and the cytosolic 90-kDa heat shock protein (Ea-hsp90A) from this species have been cloned. These cDNA revealed, respectively, 2,370 and 2,299 bp with 1,971 and 2,124 bp open reading frames encoding 656 and 707 amino acids. Main features, sequence identities and phylogenetic analysis with other species were described. Then, the expression profiles were analysed using reverse transcription/real-time quantitative PCR method from copepods subjected to different thermic and osmotic stresses in laboratory, and from copepods directly sampled into the natural population of the Seine Estuary (France) along a salinity gradient. Thermic shock (7.5°C, 22.5°C and 30°C during 90 min) significantly induced increases of transcript quantities ranged between 1.7- and 19.7-fold the levels observed in control conditions (15°C). Hypo- and hyper-osmotic shocks (salinities of 1 and 30 during 90 min) caused a 2-fold induction of Ea-hsp90A transcript level in comparison to controls (salinity of 15) whereas no significant change was measured for Ea-grp78. On the other hand, similar expression profiles were observed for the two transcripts after 72 h of exposition to salinities of 1 and 25 with a significant 2-fold induction observed for the lower salinity. To finish, strong expression inductions of both Ea-grp78 and Ea-hsp90A genes were observed in field copepods sampled at low salinity during the campaigns of June 2009 and May 2010. These results tend to show that the low salinity and the increase of temperature seem to have a synergic effect on stress condition of copepods.